THE EFFECT OF WHATSAPP CHAT GROUP MEDIA ON IMD (EARLY BREASTFEEDING INITIATION) ON KNOWLEDGE AND ATTITUDE PREGNANT MOTHERS IN BENGKULU CITY - Patroni, Rini; Sumiati, Sri (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2021)
ABSTRACTÂ Early Initiation of Breastfeeding (IMD) followed by exclusive breastfeeding is an effort to improve the health of infants and toddlers. Information about the IMD process greatly influences the formation of the intention of mothers who are about to give birth to want to implement the postpartum IMD process. Early initiation of breastfeeding (early intitasion) or early initiation of breastfeeding is that the baby begins to breastfeed itself immediately after birth. So the baby actually has the ability to breastfeed itself, as long as the baby's skin is in contact with the mother's skin, for at least one hour immediately after birth. The way babies initiate early breastfeeding is called the breast crawl or crawling looking for breasts (Utami, 2008). The method of this type of research is pre-experimental research. The population in this study were all pregnant women in the third trimester of 40. The place of research was Bengkulu City. The instrument used was a questionnaire sheet for the knowledge and attitudes of pregnant women. The results of the analysis of knowledge in the moderate category were 27 people (59.3%), and 13 people (40.7%) were in the poor category. Most of the respondents had positive attitudes about IMD, namely as many as 29 people (57.4%), and negative attitudes about IMD as many as 11 people (42.6%). Conclusion The knowledge of postpartum mothers about Early Initiation of Breastfeeding is in the sufficient category, the attitude of postpartum mothers about Early Initiation of Breastfeeding is the highest in the positive categoryÂ